Complications of Mechanical Ventilation: Nursing Assessment and Management - Alsadah, Aminah Mousa; Alhussain Mohammad Alzain; Abdiya Abdulaziz Al-Hussein; Amal Abdulaziz Al-Hussain Al-Sada; Suaad Abdulaziz Al-Hussein; Zahra Ali Ahmed Moafa; Hailah Rashed Saud Aldosari; Basmah Essa Ali Alali; Anud Eissa Ali Marzouq; Amal Ali Ahmed Qubuli; et al. (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Mechanical ventilation is a life-saving intervention for critically ill patients but is associated with significant complications, including ventilator-associated events (VAEs), ventilator-induced lung injury (VILI), and ventilator-associated pneumonia (VAP). These complications increase morbidity, mortality, and healthcare costs. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> To review the complications of mechanical ventilation and outline nursing assessment and management strategies to mitigate these risks. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This narrative review synthesizes evidence from CDC surveillance frameworks, epidemiologic studies, and clinical guidelines, focusing on pathophysiology, risk factors, and preventive strategies for VAEs, VILI, and VAP. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> VAEs occur in 5–6% of ventilated patients, with infection-related complications and VAP contributing to prolonged ICU stays and higher mortality. VILI mechanisms include atelectrauma, barotrauma, volutrauma, and biotrauma, while VAP remains a major infectious complication, often caused by multidrug-resistant organisms. Preventive strategies include lung-protective ventilation (low tidal volume, optimal PEEP), prone positioning, ECMO in severe cases, and ventilator bundles incorporating head-of-bed elevation, oral care, and sedation management. Nursing plays a pivotal role in implementing these interventions, monitoring for early deterioration, and ensuring multidisciplinary coordination. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Mechanical ventilation, while essential, carries substantial risk. Evidence-based preventive strategies and vigilant nursing care are critical to reducing complications and improving outcomes.